2018
DOI: 10.1021/acs.inorgchem.8b01818
|View full text |Cite
|
Sign up to set email alerts
|

Bioinorganic Chemistry of the Natural [Fe(NO)2] Motif: Evolution of a Functional Model for NO-Related Biomedical Application and Revolutionary Development of a Translational Model

Abstract: Identification of the distinctive electron paramagnetic resonance signal at g = 2.03 in the yeast cells and liver of mice treated with carcinogens opened the discovery and investigation of the natural [Fe­(NO)2] motif in the form of dinitrosyliron complexes (DNICs). In this Viewpoint, a chronological collection of the benchmark for the study of DNIC demonstrates that the preceding study of its biological synthesis, storage, transport, transformation, and function related to NO physiology inspires the biomimeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 180 publications
(371 reference statements)
1
43
0
Order By: Relevance
“… 47 , 48 On the basis of the characterization of the released NO and S/Fe K-edge XAS study, a slow oxidation of the [Fe(μ-SR) 2 Fe] core within DNIC-1 under an aerobic condition initiates the transformation of bridging [HOCH 2 CH 2 S] − ligands into the released (SCH 2 CH 2 OH) 2 , which weakens the Fe-to-NO π-backbonding interaction to trigger the complete release of nitric oxide and the assembly of a ferric complex ( Scheme S1a ). 37 , 46 …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 47 , 48 On the basis of the characterization of the released NO and S/Fe K-edge XAS study, a slow oxidation of the [Fe(μ-SR) 2 Fe] core within DNIC-1 under an aerobic condition initiates the transformation of bridging [HOCH 2 CH 2 S] − ligands into the released (SCH 2 CH 2 OH) 2 , which weakens the Fe-to-NO π-backbonding interaction to trigger the complete release of nitric oxide and the assembly of a ferric complex ( Scheme S1a ). 37 , 46 …”
Section: Results and Discussionmentioning
confidence: 99%
“… 34 36 Inspired by natural DNIU [Fe(NO) 2 ], biomimetic study was reported to explore mononuclear {Fe(NO) 2 } 9 dinitrosyl iron complexes (DNICs) [(NO) 2 Fe(SR) 2 ] − (or [(NO) 2 Fe(L) 2 ] − ) featuring a distinctive electron paramagnetic resonance (EPR) signal at g = 2.03, which is consistent with protein-bound DNICs ( Table S1 ). 37 Moreover, interconversions among mononuclear DNICs [(NO) 2 Fe(SR) 2 ] − /[(NO) 2 Fe(SR′) 2 ] − and dinuclear DNIC [(NO) 2 Fe(μ-SR) 2 Fe(NO) 2 ] disclosed alternative mechanisms projecting on the biological delivery of DNIU [Fe(NO) 2 ]. 36 , 37 On the one hand, the transfer of DNIU [Fe(NO) 2 ] from glutathione-bound DNIC to human glutathione transferase (GST P1–1) yielding crystallographically characterized [(NO) 2 Fe(SR)(GST-Tyr7)] (SR = glutathione) unraveled the conversion of low-molecular-weight DNIC into the protein-bound form through a ligand exchange pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the very weak signals of N 1s spectra of 1‐C , 3‐C , 4‐C , and 5‐C , a significant signal (400.0 eV) found in 6‐C was assigned to the residual TMEDA ligand (Figure S6). It is concluded that the major electrodeposition products derived from the extended electrolysis of 1.0 M Na 2 SO 4 aqueous solution and DNICs 1 / 3 – 6 are iron(III) oxides and the trace organic ligands on the surface of working electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous investigation, the cyclic voltammetric studies of DNICs reveal two reversible one‐electron redox states associated with {Fe(NO) 2 } 9 ↔{Fe(NO) 2 } 10 ↔[{Fe(NO) 2 } 10 ‐L • ] − redox states, implicating the possibilities of DNICs to promote versatile chemical reactions associated with two‐electron HER process . Recently, we demonstrated that the {Fe(NO) 2 } 10 dinitrosyl iron complex (DNIC) [(PMDTA)Fe(NO) 2 ] (PMDTA = pentamethyldiethylene triamine) plays a significant role in triggering electrocatalytic HER in neutral 1.0 M KCl aqueous solution, through the reversible redox shuttling among {Fe(NO) 2 } 9 , {Fe(NO) 2 } 10 , and reduced‐state [{Fe(NO) 2 } 10 ] electronic states .…”
Section: Introductionmentioning
confidence: 99%